The Impact of Pollution on China Marine Fishery Culture: An Econometric Analysis of Heterogeneous Growth - Yuan, Bin; Yue, Fangzhou; Wang, Xueye; Xu, Hanxiao (Frontiers in Marine Science, 2021)
The damage caused by pollution is not equal due to the differences between the marginal damage of pollution and the coping ability of the subject. Identifying the different impacts of environmental pollution on agricultural economic growth and the sources of the pollution is of great reference significance for realizing the organic integration of ecological protection and relative poverty control. This paper takes marine fishery as an example, with the production data of 53 coastal cities in China from 1994 to 2018, and empirically tests the heterogeneous effects of environmental pollution on fishery economy growth by constructing a theoretical analysis framework of heterogeneity of pollution damage. Results show that the deepening of marine environmental pollution will reduce the growth rate of marine aquaculture output, emerging significant regional differences. Nevertheless, under the background of severe environmental situation currently, different damages mainly derives from the difference of the ability to deal with environmental pollution rather than the difference of pollution degree. In terms of different wastewater sources, the impact of industrial wastewater discharge on marine fishery production is not very significant. In contrast, the adverse shocks of urban domestic sewage is more prominent. Notably, the impact of environmental pollution has a significant cumulative effect, and this negative impact is just irreversible. Therefore, the aggravation of environmental pollution will further widen the the gap in output levels between regions. Based on this, in the follow-up process of environmental pollution control, we should fully consider the different characteristics of the coping ability of the individual. While promoting industrial wastewater emission reduction, we should lay emphasis on strengthening the urban domestic sewage treatment strategies and measures, so as to give overall consideration to the ecological environment treatment and regional coordinated development.